Diaphragm, preparation method of modified fluorine-containing polymer and battery

By using the modified PVDF-HFP material in the diaphragm, the crystal and crystallinity of the supercritical carbon dioxide are used to use the supercritical carbon dioxide processing to solve the contradiction between the septum adhesion performance and the infiltration of the electrolyte, and realize the high energy efficiency and low ion impedance impedance Battery performance.

CN119361968APending Publication Date: 2025-01-24XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411455083.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

While improving the bonding performance, existing separators can easily lead to a decrease in the wettability of the electrolyte and an increase in ionic impedance, affecting the energy efficiency of the battery.

Method used

Adopt modified polytarin fluoride-hexfluoropylne (PVDF-HFP) as a rubber layer material, adjust its crystal proportion and crystal through supercritical carbon dioxide treatment, so that it has high adhesion intensity at room temperature and improves ionic ions Directive rate.

Benefits of technology

While improving the diaphragm adhesion performance, reducing ion impedance, improving the energy efficiency of the battery, and effectively suppressing the occurrence of wrinkles in the negative pole interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361968A_ABST
    Figure CN119361968A_ABST
Patent Text Reader

Abstract

The invention provides a diaphragm, a preparation method of a modified fluorine-containing polymer and a battery. The diaphragm comprises a base membrane and an adhesive layer, and the adhesive layer is arranged on at least one side surface of the base membrane; the adhesive layer comprises modified polyvinylidene fluoride-hexafluoropropylene, the weight percentage of an alpha crystal form in the modified polyvinylidene fluoride-hexafluoropropylene is M1, the weight percentage of a beta crystal form in the modified polyvinylidene fluoride-hexafluoropropylene is M2, the weight percentage of a gamma crystal form in the modified polyvinylidene fluoride-hexafluoropropylene is M3, M1 is larger than 0 and smaller than or equal to 10%, M2 is larger than or equal to 10% and smaller than or equal to 25%, M3 is larger than 0 and smaller than or equal to 10%, and the crystallinity of the modified polyvinylidene fluoride-hexafluoropropylene is not larger than 32%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a diaphragm, a preparation method of a modified fluorine-containing polymer, and a battery. Background Art

[0002] Secondary batteries (such as lithium-ion batteries) are usually composed of a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the separator is located between the positive electrode sheet and the negative electrode sheet to separate the positive and negative electrodes and prevent the two electrodes from contacting and short-circuiting.

[0003] In order to improve the bonding performance of the diaphragm, a sticky coating needs to be provided on the diaphragm. However, conventional sticky coatings will affect the electrolyte wettability of the diaphragm, increase the ionic impedance of the diaphragm, and are not conducive to improving the energy efficiency of the battery. Summary of the invention

[0004] In order to solve the above technical problems, the present application discloses a diaphragm, a method for preparing a modified fluorine-containing polymer and a battery, which improve the energy efficiency of the battery while improving the bonding performance of the diaphragm.

[0005] In a first aspect, the present application provides a diaphragm, comprising: a base film and an adhesive layer, wherein the adhesive layer is disposed on at least one side surface of the base film;

[0006] The adhesive layer includes modified polyvinylidene fluoride-hexafluoropropylene, in which the weight percentage of α crystal is M1, the weight percentage of β crystal is M2, the weight percentage of γ crystal is M3, 0<M1≤10%, 10%≤M2≤25%, 0<M3≤10%, and the crystallinity of the modified polyvinylidene fluoride-hexafluoropropylene is not more than 32%.

[0007] In some embodiments of the present application, the modified polyvinylidene fluoride-hexafluoropropylene has a crystallinity of 20% to 30%.

[0008] In some embodiments of the present application, at least one surface of the base film further includes a ceramic coating, and the adhesive layer is disposed on the surface of the ceramic coating.

[0009] In some embodiments of the present application, the diaphragm satisfies at least one of the following features:

[0010] a) the ionic resistance of the diaphragm is 0.8Ω~1.0Ω;

[0011] b) The bonding strength between the separator and the positive electrode plate is 4N / m to 8N / m;

[0012] c) The single-sided surface density of the adhesive layer is 0.3 g / m 2 ~0.8g / m 2 ;

[0013] d) the air permeability increase of the diaphragm is A, the surface density of the adhesive layer is S, and the following conditions are satisfied: 0.2≤A-22.2S≤5;

[0014] e) The weight average molecular weight of the modified polyvinylidene fluoride-hexafluoropropylene in the adhesive layer is 300,000 to 1,000,000.

[0015] In a second aspect, the present application provides a method for preparing a modified polyvinylidene fluoride-hexafluoropropylene fluorine-containing polymer, comprising the following steps:

[0016] Immersing polyvinylidene fluoride-hexafluoropropylene powder in supercritical carbon dioxide for a predetermined period of time to obtain a mixed solution, wherein the temperature of the supercritical carbon dioxide is 25° C. to 50° C. and the pressure is 5 MPa to 20 MPa;

[0017] The mixed liquid is stirred, and after the carbon dioxide in the mixed liquid is volatilized by reducing the pressure, a modified polyvinylidene fluoride-hexafluoropropylene is obtained, wherein the weight percentage of the α crystal form in the modified polyvinylidene fluoride-hexafluoropropylene is M1, the weight percentage of the β crystal form is M2, and the weight percentage of the γ crystal form is M3, 0<M1≤10%, 10%≤M2≤25%, 0<M3≤10%, and the crystallinity of the modified polyvinylidene fluoride-hexafluoropropylene is not more than 32%.

[0018] In some embodiments of the present application, in the modified polyvinylidene fluoride-hexafluoropropylene, the molar ratio of vinylidene fluoride to hexafluoropropylene is (1-9):1.

[0019] In some embodiments of the present application, the preparation method satisfies at least one of the following characteristics:

[0020] a) the temperature of the supercritical carbon dioxide is 31.5°C to 40°C, and the pressure is 8MPa to 15MPa;

[0021] b) the predetermined duration is 5 minutes to 20 minutes;

[0022] c) The stirring speed of the stirring treatment is 500 rpm to 2000 rpm, and the stirring time is 1 h to 3 h.

[0023] In a third aspect, the present application provides a battery, comprising the separator described in the first aspect.

[0024] In a fourth aspect, the present application provides an energy storage device, comprising a housing and at least one battery as described in the third aspect, wherein the battery is accommodated in the housing.

[0025] In a fifth aspect, the present application provides an electrical device, comprising the energy storage device described in the fourth aspect, wherein the energy storage device supplies power to the electrical device.

[0026] Compared with the prior art, this application has at least the following beneficial effects:

[0027] The present application provides a preparation method of a diaphragm, a modified fluorine-containing polymer and a battery, wherein the diaphragm includes a base film and a glue layer, and the glue layer is arranged on at least one side surface of the base film; the glue layer includes modified polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), the weight percentage of the α crystal form in the modified PVDF-HFP is M1, the weight percentage of the β crystal form is M2, the weight percentage of the γ crystal form is M3, 0<M1≤10%, 10%≤M2≤25%, 0<M3≤10%, and the crystallinity of the modified PVDF-HFP is not more than 32%. In the modified PVDF-HFP of the present application, the α-crystalline, β-crystalline and γ-crystalline PVDF-HFP are within the above range, and the modified PVDF-HFP has a lower crystallinity, so that the diaphragm containing the modified PVDF-HFP has a high bonding strength after pressing at room temperature, thereby improving the diaphragm's ability to suppress wrinkles at the interface of the electrode plate, and the modified PVDF-HFP of the present application can improve the ionic conductivity of the diaphragm and improve the energy efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1a This is a schematic diagram of the structure of a diaphragm according to an embodiment of the present application;

[0030] Figure 1b A schematic diagram of the structure of a diaphragm according to another embodiment of the present application;

[0031] Figure 2 This is a schematic structural diagram of a diaphragm according to another embodiment of the present application;

[0032] Figure 3 A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;

[0033] Figure 4 A schematic diagram of the structure of an energy storage system according to an implementation scheme of the present application;

[0034] Figure 5 This is a photo of the negative electrode piece of the battery of Comparative Example 1 disassembled after being fully charged;

[0035] Figure 6 This is a photo of the negative electrode piece of the battery of Example 1 disassembled after being fully charged;

[0036] Figure 7 is a scanning electron microscope (SEM) image of the glue-coated diaphragm of Example 1;

[0037] Figure 8 This is the SEM image of the glue-coated diaphragm of Comparative Example 1;

[0038] Fig. 9 This is a SEM image of the positive electrode sheet after peeling of Example 1;

[0039] Fig.10 This is the SEM image of the positive electrode sheet after peeling of Comparative Example 1.

[0040] Explanation of the reference numerals: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 10-base film, 20-glue layer, 11-ceramic coating, 400-energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.

[0043] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0044] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0045] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0046] It should be noted that, in the content of the present application, lithium-ion batteries are used as an example of batteries to explain the present application, but the batteries of the present application are not limited to lithium-ion batteries.

[0047] The present application provides a diaphragm, such as Figure 1a As shown, it includes a base film 10 and a glue layer 20, and the glue layer 20 is disposed on at least one side of the base film 10. In one embodiment, the glue layer 20 is disposed on the side of the base film 10 facing the positive electrode sheet; in another embodiment, the glue layer 20 is disposed on the side of the base film 10 facing the negative electrode sheet; in another embodiment, Figure 1b As shown, the glue layer 20 is disposed on both sides of the base film 10, and the two sides of the base film 10 face the positive electrode sheet and the negative electrode sheet respectively.

[0048] The adhesive layer 20 includes modified PVDF-HFP, in which the weight percentage of α crystal is M1, the weight percentage of β crystal is M2, and the weight percentage of γ crystal is M3, 0<M1≤10%, 10%≤M2≤25%, 0<M3≤10%. For example, M1 is 1%, 3%, 5%, 7% or 10%, M2 is 10%, 15%, 20%, 22% or 25%, and M3 is 1%, 3%, 5%, 7% or 10%. The crystallinity of the modified PVDF-HFP is not greater than 32%, for example, the crystallinity of the modified PVDF-HFP is 22%, 25%, 27%, 30% or 32%.

[0049] In the modified PVDF-HFP of the present application, the α-crystalline, β-crystalline and γ-crystalline PVDF-HFP are within the above range, and the modified PVDF-HFP has a lower crystallinity, so that the diaphragm containing the modified PVDF-HFP has a high bonding strength after being pressed at room temperature, thereby improving the ability of the diaphragm to suppress wrinkles at the interface of the electrode plate, and the modified PVDF-HFP of the present application can improve the ionic conductivity of the diaphragm, improve the energy efficiency of the lithium-ion battery, and thus improve the energy efficiency of the energy storage device when applied to the energy storage device.

[0050] In an optional embodiment, the crystallinity of the modified PVDF-HFP is 20% to 30%, for example, the crystallinity of the modified PVDF-HFP is 20%, 26%, 28% or 30%. The modified PVDF-HFP of the present application has a lower crystallinity, which is beneficial to improve the bonding strength of the diaphragm and reduce the ionic conductivity.

[0051] In an alternative embodiment, see Figure 2 , at least one surface of the base film 10 further includes a ceramic coating 11, and the adhesive layer 20 is arranged on the surface of the ceramic coating 11. In this way, it is beneficial to further improve the mechanical strength of the diaphragm. The present application has no special restrictions on the ceramic material of the ceramic coating, for example, it may include but is not limited to alumina, boehmite, etc. The present application has no special restrictions on the thickness of the ceramic coating, as long as the purpose of the present application can be achieved. For example, the thickness of the ceramic coating is 1μm to 10μm.

[0052] In an optional embodiment, the ionic impedance of the separator is 0.8Ω to 1.0Ω, for example, the ionic impedance of the separator is 0.8Ω, 0.83Ω, 0.85Ω or 1.0Ω. The ionic impedance of the separator of the present application is within the above range, which is conducive to improving the energy efficiency of the lithium-ion battery.

[0053] In an optional embodiment, the bonding strength between the diaphragm and the positive electrode plate is 4N / m to 8N / m. For example, the bonding strength between the diaphragm and the positive electrode plate is 4N / m, 5N / m, 6N / m or 8N / m. By regulating the bonding strength between the diaphragm and the positive electrode plate within the above range, during the cycle of the lithium-ion battery, the diaphragm is less likely to be peeled off from the positive electrode plate, thereby improving the structural stability of the lithium-ion battery.

[0054] In an optional embodiment, the single-sided surface density of the adhesive layer is 0.3 g / m 2 ~0.8g / m 2 For example, the single-sided surface density of the adhesive layer is 0.3g / m 2 , 0.5g / m 2 , 0.6g / m 2 or 0.8g / m 2By adjusting the single-sided surface density of the adhesive layer within the above range, it is beneficial to reduce the risk of pore plugging while improving the bonding strength of the diaphragm, thereby reducing the impact on the air permeability and ionic impedance of the diaphragm.

[0055] In an optional embodiment, the air permeability increase of the diaphragm is A, and the surface density of the adhesive layer is S, which satisfies: 0.2≤A-22.2S≤5. For example, A-22.2S is 0.2, 1.0, 3.0 or 5.0. By regulating A and S to satisfy the above relationship, it is beneficial to strictly control the air permeability of the diaphragm while improving the bonding strength of the diaphragm, thereby improving the energy efficiency of the lithium-ion battery while improving the bonding performance of the diaphragm.

[0056] The present application has no particular limitation on the weight average molecular weight of the modified PVDF-HFP in the adhesive layer, as long as the purpose of the present application can be achieved. In an optional embodiment, the weight average molecular weight of the modified PVDF-HFP in the adhesive layer is 300,000 to 1,000,000.

[0057] The present application has no particular restrictions on the content of modified PVDF-HFP in the adhesive layer, as long as the purpose of the present application can be achieved. In an optional embodiment, based on the mass of the adhesive layer, the mass percentage of modified PVDF-HFP is 40% to 80%. The remaining components of the adhesive layer may include but are not limited to other binders, dispersants and surfactants, etc. The above remaining components can be adjusted by technicians according to actual process requirements, and the present application has no particular restrictions.

[0058] The present application also provides a method for preparing a modified fluorine-containing polymer, comprising the following steps:

[0059] Step A, immersing PVDF-HFP powder in supercritical carbon dioxide for a predetermined time to obtain a mixed solution, wherein the temperature of the supercritical carbon dioxide is 25°C to 50°C, preferably 31.5°C to 40°C; the pressure is 5MPa to 20MPa, preferably 8MPa to 15MPa;

[0060] Step B, stirring the mixed solution, and after reducing the pressure to volatilize the carbon dioxide in the mixed solution, obtaining a modified PVDF-HFP, that is, a modified fluorine-containing polymer, wherein the weight percentage of the α crystal form in the modified PVDF-HFP is M1, the weight percentage of the β crystal form is M2, and the weight percentage of the γ crystal form is M3, 0<M1≤10%, 10%≤M2≤25%, 0<M3≤10%, and the crystallinity of the modified PVDF-HFP is not more than 32%.

[0061] In step A, the preparation of modified PVDF-HFP can be carried out in a reactor. The present application can use commercially available PVDF-HFP powder, and the present application has no particular restrictions on the particle size of the PVDF-HFP powder, for example, the average particle size D50 of the PVDF-HFP powder is 4 μm to 12 μm. The temperature and pressure of the supercritical carbon dioxide (SC-CO2) before mixing are regulated within the above range, the purpose of which is to make the carbon dioxide reach a supercritical state, thereby more fully swelling the PVDF-HFP.

[0062] The supercritical carbon dioxide of the present application is a fluid whose temperature and pressure are both higher than its critical point (Tc>31.1°C, Pc>7.38MPa). At this time, the interface between its gas / liquid phase disappears, it is non-toxic and tasteless, its viscosity is close to that of gas, it has no side reactions, and it has good fluidity, diffusivity, excellent dilution capacity and mass transfer rate.

[0063] In step B, as the stirring proceeds, the pressure and temperature in the reactor gradually increase, the proportion of α-crystal of PVDF-HFP decreases, the proportion of β-crystal increases, the proportion of γ-crystal increases slightly, and the proportion of amorphous phase increases, so the crystallinity decreases and the glass transition temperature also decreases; under high pressure, as the temperature increases, the proportion of α-crystal of PVDF-HFP increases slightly, the proportion of β-crystal does not change much, and the proportion of γ-crystal increases slightly, but because the proportion of amorphous phase also increases, the overall crystallinity decreases and the glass transition temperature also decreases; in the reactor, the increase in temperature under high pressure will reduce the solubility of SC-CO2 in PVDF-HFP, weaken the penetration of SC-CO2 into PVDF-HFP, that is, weaken the crystallinity reduction and crystal transformation effect of SC-CO2 on PVDF-HFP.

[0064] The decompression process of the present application can be to decompress the reactor to the ambient pressure (eg, 1 atmosphere), the decompression time is 0s to 30s, and the outlet pressure of the pressure reducing valve is 0.1MPa to 1.2MPa.

[0065] The present application provides a preparation method of modified PVDF-HFP. Under the premise of not increasing the -HFP doping amount, SC-CO2 is used to treat PVDF-HFP powder under high pressure. CO2 can produce electrostatic intermolecular interaction with the CF bond of PVDF-HFP. The high permeability of SC-CO2 allows CO2 to penetrate into the gaps between PVDF molecular chains, causing its volume to expand slightly, that is, partial swelling. The temperature and pressure of SC-CO2 are adjusted to change the proportion of different crystal forms in PVDF-HFP, so that the proportion of α crystal form is reduced and the proportion of β crystal form is increased (β crystal form has good piezoelectricity because the molecular chain is arranged in the crystal lattice in an all-trans conformation); and CO2 will dissolve in the amorphous phase of PVDF. shaped area, penetrates into the non-crystalline layer of the layered stack, relaxes the crystals, promotes more disordered stacking expansion, increases the proportion of amorphous phase (non-crystalline area), thereby reducing the crystallinity of PVDF-HFP, and the glass transition temperature decreases accordingly, so that the prepared diaphragm has high bonding strength under room temperature pressing conditions; and, during the decompression process, as the CO2 evaporates under reduced pressure, the surface of the PVDF is swelled and the softening property is solidified. This property makes the modified PVDF-HFP easy to gel adsorb in the electrolyte, forming an effect similar to that of PVDF gel electrolyte, thereby producing a strong bonding effect and ion conductivity effect on the positive electrode sheet, which can improve the bonding performance of the diaphragm while reducing the ionic impedance.

[0066] In an optional embodiment, in the modified PVDF-HFP, the molar ratio of vinylidene fluoride (VDF) to hexafluoropropylene (HFP) is (1-9): 1. For example, the molar ratio of VDF to HFP is 1: 1, 3: 1, 5: 1 or 9: 1. The molar ratio of VDF to HFP in the modified PVDF-HFP can be regulated by regulating the molar ratio of VDF to HFP in the polyvinylidene fluoride-hexafluoropropylene copolymer raw material.

[0067] In an optional embodiment, the predetermined time is 5 minutes to 20 minutes. For example, the predetermined time is 5 minutes, 10 minutes or 20 minutes, which is conducive to the full immersion and penetration of SC-CO2 into PVDF-HFP, thereby improving the shearing effect of SC-CO2 on the crystalline and non-crystalline regions of PVDF-HFP during the stirring process, and improving the conversion efficiency of different crystal proportions.

[0068] In an optional embodiment, the stirring speed of the stirring treatment is 500rpm to 2000rpm, and the stirring time is 1h to 3h. For example, the stirring speed is 500rpm, 1000rpm or 2000rpm, and the stirring time is 1h, 2h or 3h. By regulating the stirring speed and stirring time within the above range, the crystal form ratio of PVDF-HFP under the action of SC-CO2 is adjusted, which is conducive to obtaining a modified PVDF-HFP with low crystallinity.

[0069] The present application has no particular restrictions on the preparation method of the adhesive-coated diaphragm, wherein the adhesive layer can be prepared by micro-gravure coating, rotary spraying, etc., as long as a diaphragm having the adhesive layer of the present application can be obtained. Exemplarily, the diaphragm can be prepared by the following method:

[0070] The adhesive layer solution containing the modified PVDF-HFP of the present application is sprayed on at least one side of the surface of the base film by a rotary spraying device, and a diaphragm with an adhesive layer is obtained after drying. Among them, the speed of the dispersion disk can be 5000rpm to 8000rpm, the speed of the base film can be 60m / min to 120m / min, and the drying temperature is 65℃ to 85℃. The technicians can adjust it according to the actual process needs, and this application has no special restrictions.

[0071] The present application has no particular limitation on the method for preparing the above-mentioned glue layer solution. For example, the glue layer solution can be prepared by the following method:

[0072] Add deionized water as a solvent to the blender, then add the weighed polyacrylic acid (PAA) glue solution, stir evenly, then add the modified PVDF-HFP powder, continue to stir evenly, then add additives such as acrylic emulsion and surfactant, continue to stir evenly to obtain a glue layer solution.

[0073] The viscosity of the prepared adhesive layer solution is not more than 200mPa.s, the solid content is 10% to 15%, and the pH is 5 to 9. The technicians can adjust it according to the actual process needs, and there is no special limitation in this application. Among them, the acrylic emulsion includes but is not limited to methyl acrylate, butyl acrylate, ethyl acrylate and 2-ethylhexyl acrylate; the surfactant includes but is not limited to polyethylene glycol, polyethylene oxide, polyetheretherketone, polysiloxane, etc.

[0074] The present application also provides a battery, comprising the separator described in any of the above embodiments.

[0075] The lithium-ion battery of the present application also includes a positive electrode sheet. The present application has no special restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet usually includes a positive current collector and a positive electrode material layer. The positive electrode material layer can be arranged on one surface in the thickness direction of the positive current collector, or on two surfaces in the thickness direction of the positive current collector. In the present application, the positive electrode material layer is arranged on the surface of the positive current collector, that is, the positive electrode material layer can be arranged in a partial area of ​​one surface of the positive current collector, or in the entire area of ​​one surface of the positive current collector. In the present application, there is no special restriction on the positive current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the positive electrode material layer of the present application can be 8μm to 15μm.

[0076] In the present application, the positive electrode active material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, it may include at least one of lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide and lithium iron manganese phosphate.

[0077] In the present application, the positive electrode active material layer may also include a positive electrode binder. The present application has no particular limitation on the positive electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of fluorine-containing resins, polypropylene resins, fiber-type binders, rubber-type binders or polyimide-type binders.

[0078] The lithium-ion battery of the present application also includes a negative electrode sheet. The present application has no special restrictions on the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet generally includes a negative electrode collector and a negative electrode material layer. The negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode collector. In the present application, the negative electrode material layer is arranged on the surface of the negative electrode collector, that is, the negative electrode material layer can be arranged in a partial area of ​​one surface of the negative electrode collector, or in the entire area of ​​one surface of the negative electrode collector. The present application has no special restrictions on the negative electrode collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the negative electrode material layer of the present application can be 70μm to 200μm.

[0079] In the present application, the negative electrode material layer includes a negative electrode material, wherein the negative electrode material is not particularly limited as long as the purpose of the present application can be achieved. For example, it may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, and silicon carbon.

[0080] In the present application, the negative electrode material layer may further include a negative electrode binder. The present application has no particular restrictions on the negative electrode binder, as long as it can achieve the purpose of the present application, for example, it may include but is not limited to at least one of acrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, and potassium carboxymethyl cellulose.

[0081] The present application has no particular restrictions on the base film of the diaphragm, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, the base film is a non-woven fabric, film or composite film with a porous structure, and the material of the base film is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film can be selected. The present application has no particular restrictions on the thickness of the base film, as long as the purpose of the present application can be achieved. Exemplarily, the thickness of the base film is 5μm to 20μm.

[0082] The battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is mixed in a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, and then a lithium salt is added to dissolve and mix evenly. The present application has no restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the lithium salt is 1.0 mol / L to 2.0 mol / L.

[0083] The battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.

[0084] The present application does not particularly limit the preparation method of the battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a battery.

[0085] The present application also provides an energy storage device, including a housing and at least one battery in any of the above embodiments, wherein the battery is contained in the housing. The energy storage device having the battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more batteries, and when the energy storage device contains multiple batteries, the multiple batteries may be connected in at least one of parallel and series connection.

[0086] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical device. In an optional implementation scheme, the electrical device includes an electrical device body, and the energy storage device is used to supply power to the electrical device body. In an optional implementation scheme, the electrical device body includes a positive electrode of the device and a negative electrode of the device, the positive electrode plate of the battery in the energy storage device is used to electrically connect to the positive electrode of the device body of the electrical device, and the negative electrode plate of the battery in the energy storage device is used to electrically connect to the negative electrode of the device body of the electrical device, so as to supply power to the electrical device.

[0087] The electrical equipment of the present application may include but is not limited to: containers, household energy storage systems, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.

[0088] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 3The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.

[0089] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.

[0090] See also Figure 4 , Figure 4 This is a schematic diagram of the structure of an energy storage system 400 according to an implementation scheme of the present application, and the present application Figure 4 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.

[0091] The present application provides an energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak shaving, frequency regulation, standby and other services for the power grid operation, giving full play to the peak shaving role of the power grid, promoting peak shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.

[0092] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0093] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.

[0094] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple batteries of the present application, and the battery system may be a charging and discharging system including the battery or battery pack of the present application.

[0095] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 is a single battery, the energy storage device 1 may be at least one of a cylindrical battery, a square battery, and the like.

[0096] The diaphragm and the preparation method thereof of the present application are further described below in conjunction with more specific embodiments.

[0097] Example

[0098] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.

[0099] Example 1

[0100] <Preparation of Separator>

[0101] <Preparation of modified PVDF-HFP>

[0102] 5 kg of PVDF-HFP powder was added to a supercritical carbon dioxide reactor, and then about 7.5 L of liquid CO2 was injected, the temperature and pressure in the reactor were increased to make the liquid CO2 reach a supercritical state, and the PVDF-HFP powder was soaked in SC-CO2 for 10 minutes. The temperature and pressure of SC-CO2 are shown in Table 1; then the mixture of the two was stirred and sheared at a stirring speed of 1000 rpm for 2 hours, and then the reactor was depressurized to ambient pressure to volatilize the carbon dioxide in the mixture, and the product was sieved to obtain modified PVDF-HFP powder.

[0103] <Preparation of Subbing Solution>

[0104] The modified PVDF-HFP powder, PAA glue, methyl acrylate and surfactant polyethylene oxide were weighed in a mass ratio of 75:6:18:1; deionized water was first added into a stirrer as a solvent, and then the weighed PAA glue was added, and the mixture was stirred evenly at 1000 rpm / 15 min, and then the modified PVDF-HFP powder was added, and the mixture was stirred evenly at 2500 rpm / 90 min, and then the acrylic emulsion and surfactant were added, and the mixture was stirred evenly at 1000 rpm / 15 min, and then the mixture was slowly stirred at 500 rpm / 15 min to eliminate bubbles to obtain a glue layer solution.

[0105] <Preparation of Substrate Layer>

[0106] The glue layer solution is sprayed onto both sides of the base film by using a rotary spraying device. The base film is a base film with a ceramic coating on the surface. The ceramic coating thickness is 2 μm. The base film is a polyethylene (PE) porous film with a thickness of 7 μm. After drying at 65°C, a separator with a glue layer is obtained. The single-sided surface density of the glue layer is 0.3 g / m 2 , the dispersion disk speed is 5000rpm and the diaphragm belt speed is 60m / min.

[0107] <Preparation of positive electrode sheet>

[0108] The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 97:1:2; then N-methylpyrrolidone (NMP) is added as a solvent and stirred evenly to prepare a positive electrode slurry with a solid content of 60wt%, and then the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 11μm, and dried at 85℃, and then the above steps are repeated on the other surface of the positive electrode sheet, and a positive electrode sheet coated with a positive electrode material layer on both sides is obtained after rolling. The single-sided thickness of the positive electrode material layer is 100μm.

[0109] <Preparation of negative electrode sheet>

[0110] The negative electrode materials artificial graphite, conductive carbon black (Super-P) and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 96:1.5:2.5, deionized water was added, stirred evenly, and a negative electrode slurry with a solid content of 60wt% was prepared. Then the negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, dried at 105℃, and then the above steps were repeated on the other surface of the negative electrode sheet. After rolling, a negative electrode sheet with a negative electrode material layer coated on both sides was obtained, and the single-side thickness of the negative electrode material layer was 70μm.

[0111] <Preparation of Electrolyte>

[0112] Ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1, dissolved, and fully stirred, and then placed in an environment of 5°C or less for 12 hours, and then lithium hexafluorophosphate (LiPF6) is added and mixed evenly to obtain an electrolyte. The molar concentration of LiPF6 in the electrolyte is 1.0 mol / L.

[0113] <Preparation of lithium-ion batteries>

[0114] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode and the negative electrode to play an isolating role, and wound to obtain a bare cell. The bare cell is placed in an aluminum-plastic film packaging bag, vacuum dried, and then injected with electrolyte, and a lithium-ion battery is obtained through vacuum packaging, standing, and formation processes.

[0115] Embodiment 2 to Embodiment 3

[0116] Except that in <Preparation of Diaphragm>, the temperature and pressure of SC-CO2 are adjusted according to Table 1, and the proportion of α-crystal, β-crystal and γ-crystal and the crystallinity in the modified PVDF-HFP change accordingly, the rest is the same as Example 1.

[0117] Example 4

[0118] Except that in <Preparation of Diaphragm>, the temperature and pressure of SC-CO2 are adjusted according to Table 1, the proportion of α-crystal, β-crystal and γ-crystal and the crystallinity in the modified PVDF-HFP change accordingly, and the single-sided surface density of the adhesive layer is adjusted according to Table 2, the rest is the same as Example 1.

[0119] Embodiment 5 to Embodiment 8

[0120] Except that in <Preparation of Diaphragm>, the temperature and / or pressure of SC-CO2 is adjusted according to Table 1, and the proportion of α-crystal, β-crystal and γ-crystal and the crystallinity in the modified PVDF-HFP change accordingly, the rest is the same as Example 4.

[0121] Embodiment 9-embodiment 10

[0122] Except that the single-sided surface density of the adhesive layer was adjusted according to Table 2 in <Preparation of Separator>, the rest was the same as Example 4.

[0123] Example 11 to Example 15

[0124] Except that the predetermined duration of immersion, stirring speed, and stirring time are adjusted according to Table 3 in <Preparation of Diaphragm>, the rest is the same as Example 4.

[0125] Comparative Example 1

[0126] Except that PVDF-HFP is directly used in <Preparation of Diaphragm>, that is, PVDF-HFP is not modified, the rest is the same as Example 1.

[0127] Comparative Example 2 to Comparative Example 3

[0128] Except that in <Preparation of Diaphragm>, the temperature and pressure of SC-CO2 are adjusted according to Table 1, and the proportion of α-crystal, β-crystal and γ-crystal and the crystallinity in the modified PVDF-HFP change accordingly, the rest is the same as Example 1.

[0129] Table 1 Preparation parameters of Examples 1 to 8 and Comparative Examples 1 to 3

[0130]

[0131] In Table 1, “ / ” indicates that there is no relevant preparation parameter.

[0132] Table 2 Preparation parameters of Examples 1 to 10

[0133] <![CDATA[Grammage per side (g / m 2 )]]> Air permeability increase (s / 100cc) Example 1 0.35 8 Example 2 0.35 9 Example 3 0.35 9 Example 4 0.80 18 Example 5 0.80 19 Example 6 0.80 18 Example 7 0.80 19 Example 8 0.80 21 Example 9 0.50 12 Example 10 0.70 17

[0134] Table 3 Preparation parameters of Example 4, Example 11 to Example 15

[0135]

[0136] Test methods and equipment

[0137] Crystallinity test:

[0138] The test was conducted in accordance with the standards GB / T 22232-2008 Determination of thermal stability of chemical substances by differential scanning calorimetry and GB / T19466-3-2004 Plastics differential scanning calorimetry (DSC) Part 3: Determination of melting and crystallization temperature and enthalpy. The test temperature was first heated to 380°C and then cooled to room temperature; the heating rate and cooling rate were both 10°C / min, and the nitrogen atmosphere was used for protection. The crystallinity is the ratio of the melting enthalpy of the DSC test to the theoretical 100% complete crystallization melting enthalpy. The melting enthalpy of completely crystallized PVDF is 104.5 J / g.

[0139] Test on weight ratio of different crystal forms in PVDF-HFP:

[0140] Infrared test and analysis were carried out according to the standards "GB / T 32199-2015 General Rules for Qualitative Analysis of Infrared Spectroscopy" and "GB / T7764-2017 Infrared Spectroscopy for Rubber Identification". Test range: 4000 -1 ~400cm -1, record the absolute intensity and relative intensity of each characteristic absorption peak, use the relative intensity of the infrared absorption peaks corresponding to the three different crystals of α, β, and γ to accumulate, and then make a ratio with the total relative intensity to obtain the different proportions of the three crystal phases of α, β, and γ, and then multiply by the crystallinity to obtain the weight proportion of the three crystal phases of α, β, and γ. The Fourier transform infrared spectroscopy (FTIR) exclusive characteristic absorption peaks of different crystal forms of PVDF-HFP are shown in Table 4.

[0141] Table 4 FTIR specific characteristic absorption peaks of different crystalline forms of PVDF-HFP

[0142]

[0143] Single-sided surface density test of adhesive layer:

[0144] The test was carried out according to the standard "GB / T 20220-2006 Plastic film and sheet sample average thickness, roll average thickness and unit mass area determination weighing method", using a 100cm 2 Use a gram weight sampler to cut 5 pieces of base film and 5 pieces of diaphragm with glue layer respectively, weigh them respectively to get the mass, and then divide the mass by the sampling area to get their respective surface densities. The difference between the two is the surface density of the glue coating. Test 5 times and take the average value.

[0145] Bond strength test between diaphragm and positive electrode:

[0146] The peel strength test of the separator-positive electrode sheet with adhesive layer was carried out with reference to the standard "GB / T 2792-2014 Test method for peel strength of adhesive tape". After pressing, the sample size was cut to 20mm*100mm, fixed in the middle of the clamp of the tensile machine, and then the tensile machine was used to peel the separator and the positive electrode sheet at a speed of 50mm / min along the 180° direction. The test distance was up to 80mm, and the average value was taken for 5 tests. The bonding force was the average value of the peel strength. The pressing method of the separator and the positive electrode sheet is: cut the positive electrode sheet and the separator of 100mm*100mm, naturally stack them, and put them into the flat press for pressing. The room temperature pressing temperature is 25℃~30℃, the holding time is 30s~60s, and the pressure per unit area is 2MPa~7MPa.

[0147] Diaphragm ionic impedance test:

[0148] The ionic impedance of the diaphragm was tested by referring to the ionic conductivity test method in 6.6.2 of the standard "GB / T 36363-2018 Polyolefin diaphragms for lithium-ion batteries".

[0149] Lithium-ion battery energy efficiency test:

[0150] At 25°C, the lithium-ion battery was charged and discharged at 0.5P, with a charge cutoff voltage of 3.7V and a discharge cutoff voltage of 2.45V until the capacity of the lithium-ion battery reached 60% of the initial capacity. At the same time, the energy efficiency of the lithium-ion battery after 500 cycles was tested by the constant current method, energy efficiency = 500th cycle discharge energy / 500th cycle charge energy × 100%.

[0151] Negative electrode interface test after full charge:

[0152] Disassemble the fully charged cell according to the operating specifications. The humidity in the disassembly room is ≤5%RH and the temperature is 25±3℃. Take photos to record the wrinkles on the interface of the negative electrode. If the number of wrinkles on the negative electrode is 0, it is judged to be without wrinkles; if the number of wrinkles on the negative electrode is 1-3, it is judged to be very slight wrinkles; if the number of wrinkles on the negative electrode is 4-6, it is judged to be slight wrinkles; if the number of wrinkles on the negative electrode is 7 or more, it is judged to be obvious wrinkles.

[0153] Table 5 Performance data of each embodiment and comparative example

[0154]

[0155]

[0156] Combining Table 1 and Table 5, it can be seen from Examples 1 to 8 and Comparative Examples 1 to 3 that since the PVDF-HFP of Comparative Example 1 is not modified, the bonding strength between the diaphragm and the positive electrode sheet is low, the ionic impedance is high, the energy efficiency is low, and Figure 5 As shown, after full charge, the interface of the negative electrode plate has obvious wrinkles; the bonding strength between the separator and the positive electrode plate of Comparative Examples 2 and 3 is low, and the negative electrode plate also has obvious wrinkles; while the bonding strength between the separator and the positive electrode plate of the present application is higher, the ionic impedance is reduced, the energy efficiency is improved, and as shown in Figure 6 As shown, the negative electrode plate interface of the lithium-ion battery of Example 1 has no wrinkles after being fully charged. This may be due to the higher bonding strength between the diaphragm and the positive electrode plate, which in turn enables a better fit between the diaphragm and the negative electrode plate inside the lithium-ion battery, thereby improving the ability of the diaphragm to suppress the physical expansion and deformation of the negative electrode plate during the charge and discharge cycle, avoiding the undesirable phenomenon of wrinkles on the surface of the negative electrode plate, thereby continuously improving the interface wrinkles of the negative electrode plate inside the lithium-ion battery.

[0157] In combination with Table 2 and Table 5, it can also be seen from Examples 1 and 2 to 10 that, on the basis of the diaphragm having the modified PVDF-HFP of the present application, by regulating the density of the adhesive layer and the increase in the air permeability of the diaphragm to meet the relationship of the present application, it is beneficial to strictly control the air permeability of the diaphragm while improving the bonding strength of the diaphragm, thereby improving the energy efficiency of the lithium-ion battery while improving the bonding performance of the diaphragm.

[0158] In the preparation process of modified PVDF-HFP, process parameters such as immersion time, stirring speed, stirring time, etc. usually affect the performance of modified PVDF-HFP. Combining Table 3 and Table 5, it can also be seen from Examples 4 and 11 to 15 that by adjusting the above process parameters within the scope of this application, it is beneficial to obtain the modified PVDF-HFP of this application.

[0159] Figure 7 This is the SEM image of the glue-coated diaphragm of Example 1. Figure 7 It can be seen that after the PVDF-HFP powder modified by SC-CO2 is spray-coated on the base film, the surface of the primary particles partially swells, and some adhesion occurs between each other, and there are still obvious pores between the formed secondary particles, which is beneficial to improve the bonding performance of the adhesive layer;

[0160] Figure 8 The SEM image of the glue-coated diaphragm of Comparative Example 1 is shown in FIG. Figure 8 It can be seen that the primary particles of the unmodified PVDF-HFP powder maintain a relatively regular spherical shape, with no obvious swelling on the surface, and the secondary particle agglomerates formed have obvious shapes, which is not conducive to improving the bonding properties of the adhesive layer;

[0161] Fig. 9 This is the SEM image of the positive electrode sheet after peeling of Example 1. Fig. 9 It can be seen that the diaphragm with glue layer prepared from PVDF-HFP powder modified by SC-CO2 has a relatively complete outer ring connection of the glue points transferred to the positive electrode sheet after dry pressing and bonding, a larger effective bonding area, and a significantly stronger bonding effect;

[0162] Fig.10 The SEM image of the positive electrode sheet after peeling of Comparative Example 1 is shown in FIG. Fig.10 It can be seen that the diaphragm with glue layer prepared by unmodified PVDF-HFP powder has incomplete outer ring connection of glue points transferred to the positive electrode sheet after dry pressing bonding, small effective bonding area and weak bonding effect.

[0163] The above is a detailed introduction to a diaphragm, a preparation method of a modified fluorine-containing polymer and a battery disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application. At the same time, for general technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A diaphragm, characterized in that: include: A base film and an adhesive layer, wherein the adhesive layer is disposed on at least one side surface of the base film; The adhesive layer includes modified polyvinylidene fluoride-hexafluoropropylene, in which the weight percentage of α crystal is M1, the weight percentage of β crystal is M2, the weight percentage of γ crystal is M3, 0<M1≤10%, 10%≤M2≤25%, 0<M3≤10%, and the crystallinity of the modified polyvinylidene fluoride-hexafluoropropylene is not more than 32%.

2. The diaphragm according to claim 1, characterized in that The modified polyvinylidene fluoride-hexafluoropropylene has a crystallinity of 20% to 30%.

3. The diaphragm according to claim 1 or 2, characterized in that: At least one surface of the base film further includes a ceramic coating, and the adhesive layer is disposed on the surface of the ceramic coating.

4. The diaphragm according to claim 1, characterized in that The diaphragm satisfies at least one of the following characteristics: a) the ionic resistance of the diaphragm is 0.8Ω~1.0Ω; b) The bonding strength between the separator and the positive electrode plate is 4N / m to 8N / m; c) The single-sided surface density of the adhesive layer is 0.3 g / m 2 ~0.8g / m 2 ; d) the air permeability increase of the diaphragm is A, the surface density of the adhesive layer is S, and the following conditions are satisfied: 0.2≤A-22.2S≤5; e) The weight average molecular weight of the modified polyvinylidene fluoride-hexafluoropropylene in the adhesive layer is 300,000 to 1,000,000.

5. A method for preparing a modified fluorine-containing polymer, characterized in that: The following steps are involved: Immersing polyvinylidene fluoride-hexafluoropropylene powder in supercritical carbon dioxide for a predetermined period of time to obtain a mixed solution, wherein the temperature of the supercritical carbon dioxide is 25° C. to 50° C. and the pressure is 5 MPa to 20 MPa; The mixed liquid is stirred, and after the carbon dioxide in the mixed liquid is volatilized by reducing the pressure, a modified polyvinylidene fluoride-hexafluoropropylene is obtained, wherein the weight percentage of the α crystal form in the modified polyvinylidene fluoride-hexafluoropropylene is M1, the weight percentage of the β crystal form is M2, and the weight percentage of the γ crystal form is M3, 0<M1≤10%, 10%≤M2≤25%, 0<M3≤10%, and the crystallinity of the modified polyvinylidene fluoride-hexafluoropropylene is not more than 32%.

6. The preparation method according to claim 5, characterized in that: In the modified polyvinylidene fluoride-hexafluoropropylene, the molar ratio of vinylidene fluoride to hexafluoropropylene is (1-9):

1.

7. The preparation method according to claim 5 or 6, characterized in that: Satisfies at least one of the following characteristics: a) the temperature of the supercritical carbon dioxide is 31.5°C to 40°C, and the pressure is 8MPa to 15MPa; b) the predetermined duration is 5 minutes to 20 minutes; c) The stirring speed of the stirring treatment is 500 rpm to 2000 rpm, and the stirring time is 1 h to 3 h.

8. A battery, characterized in that: A diaphragm comprising the diaphragm according to any one of claims 1 to 4.

9. An energy storage device, characterized in that: The invention comprises a casing and at least one battery according to claim 8, wherein the battery is accommodated in the casing.

10. An electrical device, characterized in that: It includes the energy storage device as described in claim 9, and the energy storage device supplies power to the electrical equipment.

Citation Information

Patent Citations

  • Polyolefin microporous membrane for battery diaphragm and manufacturing method of polyolefin microporous membrane

    CN104681763A

  • Polyvinylidene fluoride-hexafluoropropylene-based lithium-ion battery composite membrane

    CN105789532A

  • Method for purifying vinylidene fluoride polymer

    CN116249723A

  • Secondary battery and device

    CN118783041A

  • Method for purifying fluororesin and fluororesin purified by the method

    JP2005089524A